A review on classes of anti diabetic drugs and synthetic methods to access them: classical and modern approaches - Shahriyar, Md. Sakif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.